Prediction Of Long-Term Quality Fluctuations In The South Field Lignite Mine Of West Macedonia - A. Pavlidis (Society for Mining, Metallurgy & Exploration, 2006)
This paper investigates variations of lignite quality attributes with geostatistical methods. The study focuses on lignite from the Southern Field in the Greek province of West Macedonia. The targeted quality variable is the ash water-free content (AWF). A geostatistical model is constructed based on data from 480 drillholes (approximate drill hole spacing of 250m). For each drillhole, the vertical average of the AWF is calculated. The coarse-grained AWF is then modeled as the superposition of a trend surface and fluctuations. The spatial dependence of the fluctuations is modeled by means of the experimental variogram. Kriging estimators are used to determine the AWF values on a rectangular grid, and the uncertainty of the estimates is calculated. Implications of the analysis for the variability of the produced lignite are discussed, and recommendations for additional drilling are proposed.